A Study of Students’ Science Experiences with Metacognitive Learning Strategies in Indonesian Elementary Schools - Hasim, Wahid; Maryani, Ika; Malana, Bita; Widodo, Hendro; Sumaryati (The Indonesian Institute of Science and Technology Research, 2025)
Students’ lack of learning awareness influences science learning loss in elementary schools due to poor metacognitive skills. Therefore, teachers need to facilitate the development of students’ metacognitive abilities, for example, by utilizing metacognition-based modules to provide an independent and engaging science education experience. The present study sought to develop a science module founded on metacognition principles, to facilitate autonomous and pleasurable learning for pupils in elementary school. We followed the research and development procedure to generate the module. A needs analysis was conducted to determine the demand for the metacognition-based module and identify student characteristics and learning challenges. The needs analysis data were collected via interviews and observation. The module was assessed by experts and tested for effectiveness through a one-group pretest-posttest experiment. The expert evaluation instrument and metacognition awareness inventory (MAI) were developed and validated. The expert validity score was determined using the Delphi technique. The qualitative data on expert judgment were analyzed descriptively, while the quantitative data on expert judgment were determined using the Aiken-V coefficient. Metacognition data were analyzed using the paired sample t-test. The expert validation score was high, indicating that the module was valid. The effectiveness test result using the t-test showed a significant difference in the study participants’ metacognitive skills before and after learning (sig = 0.000 or sig < 0.05). This study’s findings suggested that a metacognition-integrated module could facilitate the development of elementary school students’ metacognitive skills. Teachers as facilitators play a crucial role in providing instruction and assisting students in the classroom.